2017
DOI: 10.1177/0883911517707776
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of zwitterionic acrylamide copolymers for biocompatible applications

Abstract: In order to prepare acrylamide copolymers with non-toxicity for environment-friendly materials, a series of zwitterionic acrylamide copolymers with varying acrylamide content were synthesized with DMAPS (3-dimethyl (methacryloyloxyethyl) ammonium propane sulfonate) and acrylamide via free radical polymerization. The structural properties and cytotoxicity are carefully investigated. The results demonstrate that DMAPS-co-acrylamide copolymers contain DMAPS and acrylamide segments that form a matrix consisting of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…These results confirm the biocompatibility of the ZSC‐gel, consistent with the pioneering investigations on zwitterionic polymers. [ 29,30 ]…”
Section: Formulation and Characterization Of The Zsc‐gel Electrolytementioning
confidence: 99%
“…These results confirm the biocompatibility of the ZSC‐gel, consistent with the pioneering investigations on zwitterionic polymers. [ 29,30 ]…”
Section: Formulation and Characterization Of The Zsc‐gel Electrolytementioning
confidence: 99%
“…40 As for HTC-Glc-3%MSA, the sulfobetaine structure was confirmed by the presence of −SO 3 at around 1043 cm −1 and −N + (CH 3 ) 2 − at around 960 cm −1 in MSA (Figure 4e) and HTC-Glc-3%MSA (Figure 4d) according to the previously reported literature. 41,42 At the same time, the above peaks did not appear in HTC-Glc (Figure 4b), also confirming the successful grafting of two kinds of zwitterionic groups.…”
Section: ■ Results and Discussionmentioning
confidence: 54%
“…Comparing the FT-IR spectra of MPC (Figure c), HTC-Glc (Figure b), and HTC-Glc-10%MPC (Figure a), we also could see the peaks at around 1240 and 1080 cm –1 in MPC and HTC-Glc-10%MPC corresponding to the stretching vibration of PO and the stretching vibration of −POCH 2 –, as well as the peaks at around 1170 and 970 cm –1 corresponding to the stretching vibration of C–N and N + (CH 3 ) 3 . As for HTC-Glc-3%MSA, the sulfobetaine structure was confirmed by the presence of −SO 3 at around 1043 cm –1 and −N + (CH 3 ) 2 – at around 960 cm –1 in MSA (Figure e) and HTC-Glc-3%MSA (Figure d) according to the previously reported literature. , At the same time, the above peaks did not appear in HTC-Glc (Figure b), also confirming the successful grafting of two kinds of zwitterionic groups.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, it was reported that pDA coatings attenuated the toxicity effect of semiconductor quantum dots in blood and enhanced blood compatibility of materials . SB-related materials have been applied for the medical applications due to their high biocompatibility. , Accordingly, the released copper ions from the coatings cause negligible cytotoxicity, and the coatings can be regarded as biocompatible materials for medical applications.…”
Section: Resultsmentioning
confidence: 99%
“…48 SB-related materials have been applied for the medical applications due to their high biocompatibility. 49,50 Accordingly, the released copper ions from the coatings cause negligible cytotoxicity, and the coatings can be regarded as biocompatible materials for medical applications.…”
Section: ■ Results and Discussionmentioning
confidence: 99%